The Effect of Training and the Implementation of Occupational Health and Safety (OHS) Systems on Employee Productivity at PT. PP. London Sumatra Indonesia Tbk Branch Office Medan - Nora Anisa Br. Sinulingga; Sathis Rosen (Junal Ilmu Manajemen, 2020)
The purpose of this research was to determine the influence of training and occupational health and safety (OHS) on employee productivity at PT. PP. London Sumatra Indonesia Tbk Medan Branch Office. Type of this research is a quantitative research that was analyzed with multiple linear regression with SPSS Statistics 22. The data source is primary and secondary collected by using some methods: observation, interview, questionnaire, and documentation. The populations in this research is 115 person, while the samples amounted 54 correspondents which is obtained with the Slovin formula. The result of this research, based on partially and simultaneous test, proved that the training and occupational health and safety (OHS) have a significant influence on employee productivity at PT. PP. London Sumatra Indonesia Tbk Medan Branch Office.